Potential of Geographical Indications of Coffee as ​​an Effort to Improve Community Welfare in Ngresepbalong Village on the Slope of Mount Ungaran: Potensi Indikasi Geografis Kopi Sebagai Upaya Peningkatan Kesejahteraan Masyarakat Di Desa Ngresepbalong Lereng Gunung Ungaran - Mustaidah, Nurul; Waspiah, Waspiah (Annual Review of Legal Studies, 2024)
Geographical indication, this coffee can be identified as a product that comes from a particular region, which in this case the selling value and products of this coffee can increase. But in reality, the potential of geographical indications of coffee in Indonesia is still not fully utilized or used to improve the welfare of the community. This paper formulates two main issues: (1) Requirements and procedures that must be met to obtain legal protection of the potential geographical indication of coffee from Ngresepbalong Village, Ungaran Mountain Slope, 2) Potential geographical indication of coffee from Ngresepbalong Village on the slopes of Mount Ungaran as an effort to improve the welfare of the community. The method used in this writing is normative juridical research method. This normative legal research focuses on primary and secondary legal materials, namely research that leads to the norms that exist in the legislation. Based on the discussion, it can be concluded that Geographical Indications of coffee have significant potential in improving the welfare of the community in Ngresepbalong Village on the slopes of Mount Ungaran. With Geographical Indication certification, coffee produced in the area can be guaranteed to have a unique and distinctive quality, and has a high reputation in the international market. Geographical Indication of coffee can be an effective tool in improving the welfare of the people in Ngresepbalong Lereng Gunung Ungaran Village, as well as maintaining the cultural identity and traditions of the area.